VYGOTSKY’S PERSPECTIVE ON CONCEPT DEVELOPMENT IN THE CHILD AND THE ROLE OF INSTRUCTION IN IT - Sajani K Narayanan (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This theoretical paper maps down the process of concept development from Vygotsky’s theory of concept formation, the steps involved in the concept formation and the role of instruction in it. Vygotsky distinguished between lower order thinking and higher order thinking and he classified concepts into everyday concepts and scientific concepts. Scientific concepts are higher order cognitive processes as it is learnt by a child in a mediated process, in contrast to everyday concepts which are learnt through everyday experiences. Moreover, he gave the concept of the zone of proximal development and its role in the development of scientific concepts. This paper provides a detailed description of the process of concept development and the role of instruction in it.